Hindsight From 2020: Lessons to Learn From a Global Pandemic. Issue 3 (27th January 2021) - Egan, Cate A.; Sacko, Ryan S.
Abstract : This article will discuss ideas related to some of the practices that have developed in the field during the COVID-19 pandemic that may allow us to evolve as educators once this global health crisis has ended.